Analysis of Differences in Credit Distribution, Non-performing Loans and Profits of Rural Banks (BPR) with the Issuance of the Financial Services Authority - Muhammad Firdaus B. Y.; Raden Heru Kristanto; Khoirul Hikmah (UPN Veteran Yogyakarta, 2022)
This study aims to determine differences in credit distribution, non-performing loans, and profits at Rural Banks Owned by Regional Governments in DIY before and during the Covid-19 Pandemic after the issuance of Number 11/POJK.03/2020. This research was conducted by quantitative comparative method. The samples taken in this study are data regarding the level of lending, non-performing loans (NPL), and net income from the publication reports of Perumda BPR Bank Jogja, PT BPR Bank Sleman (Perseroda), PT BPR Bank Bantul (Perseroda), PD BPR Bank Kulon Progo Market, and PT BPR Bank Daerah Gunungkidul in 2018, 2019, 2020 and 2021. Data testing was carried out using a paired sample T/T-test using the SPSS program, with a significance value of 5%. The results of this study include differences in credit distribution at Rural Banks Owned by Regional Governments in the Special Region of Yogyakarta before and during the Covid-19 Pandemic after the issuance of Financial Services Authority Regulation (POJK) Number 11/POJK.03/2020, then there is no significant differences in non-performing loans of Regional Government-Owned Rural Banks in the Special Region of Yogyakarta before and during the Covid-19 Pandemic after the issuance of Financial Services Authority Regulation (POJK) Number 11/POJK.03/2020, as well as significant differences in bank profits Local Government-Owned People's Credit in the Special Region of Yogyakarta before and during the Covid-19 Pandemic after the issuance of Financial Services Authority Regulation (POJK) Number 11/POJK.03/2020.